Impact of Teacher Demonstration Video On Polytechnic Students’ Achievement in Shorthand in Zamfara State - S. Anka, Shahid,; Anthony, Aniah,; Z. Evuti, Adamu,; Mercy, Adeyeye, (Kashere Journal of Education, 2021)
The study examined the effect of teacher demonstration video on Polytechnic students’ achievement in Shorthand in Zamfara State. A pretest-posttest quasi-experimental and control group design was used in the study. A sample size of 185 students was obtained from the two intact classes of the two polytechnics that were used for this study. The polytechnics were assigned to treatment and control groups through simple random selection. The instrument for data collection was Shorthand Achievement Test (SHAT). It was validated by 3 educational technology experts and 5 Shorthand lecturers. The instrument was later subjected to reliability test and the data was computed using Pearson product Moment Correlation. A coefficient value of (r) .75 was obtained indicating that the instrument is reliable for the study. Data gathered from the field was computed and used to answer the research questions using mean and standard deviation while hypotheses were tested using t-test. All the analyses were conducted using SPSS version 23. The findings of the study revealed that significant difference exists in the Shorthand achievement scores of polytechnic students exposed to teacher demonstration video and those in the control group. It also revealed that significant difference exists in the Shorthand achievement scores of male and female polytechnic students exposed to teacher demonstration video. Based on these outcomes, the researchers recommended amongst others that Shorthand lecturers should critically examine the need, suitability in use, easy in operation and the possible benefits which is attainable in the use of video instruction in his shorthand class before deciding to apply it in order to avoid futile efforts at the end of the lesson.